Social Media Construction: Making Sense of Hadith Dissemination on Instagram - Jubba, Hasse; Long, Ahmad Sunawari; Fernando, Henky; Larasati, Yuniar Galuh; Cahyani, Novita; Harni, Mellysa Dwi (UIN Sunan Kalijaga Yogyakarta, 2023)
The proliferation of hadith dissemination on Instagram, a popular social media platform, presents a compelling avenue for exploration. This phenomenon has engendered increasingly intricate and dynamic models and characteristics of hadith disseminators. However, this development has received inadequate attention in scholarly discourse, often being overlooked. This study not only addresses the shortcomings of previous research but also delves into the question of how hadith dissemination on Instagram can shape the models and characteristics of hadith disseminators to become more contextually relevant and adaptable. To address this inquiry, this study employs a qualitative descriptive approach to examine the models and characteristics of hadith disseminators prevalent in the #hadith hashtag on Instagram. The findings not only reveal that hadith dissemination on Instagram has transcended virtual-based communication and interaction patterns but also underscore the construction of a more contextual and dynamic model and characteristics of hadith dissemination. This study additionally emphasizes the value of interviewing Instagram users to gain a more comprehensive and reflective understanding of this phenomenon.